A New Method for Large Scale Isolation of Kidney Glomeruli from Mice - Takemoto, Minoru (American Society for Investigative Pathology, 2002)
Here we report a new isolation method for mouse glomeruli. The method is fast and simple and allows for the isolation of virtually all glomeruli present in the adult mouse kidney with minimal contamination of nonglomerular cells. Mice were perfused through the heart with magnetic 4.5-μm diameter Dynabeads. Kidneys were minced into small pieces, digested by collagenase, filtered, and collected using a magnet. The number of glomeruli retrieved from one adult mouse was 20,131 ± 4699 (mean ± SD, n = 14) with a purity of 97.5 ± 1.7%. The isolated glomeruli retained intact morphology, as confirmed by light and electron microscopy, as well as intact mRNA integrity, as confirmed by Northern blot analysis. The method was applicable also to newborn mice, which allows for the isolation of immature developmental stage glomeruli. This method makes feasible transcript profiling and proteomic analysis of the developing, healthy and diseased mouse glomerulus.